Positive effect of dapagliflozin on left ventricular longitudinal function for type 2 diabetic mellitus patients with chronic heart failure - Tanaka, Hidekazu (Cardiovasc Diabetol, 2020)
BACKGROUND: The effect of sodium glucose cotransporter type 2 (SGLT2) inhibitor on left ventricular (LV) longitudinal myocardial function in type 2 diabetes mellitus (T2DM) patients with heart failure (HF) has remained unclear. METHODS: We analyzed data from our previous prospective multicenter study, in which we investigated the effect of the SGLT2 inhibitor dapagliflozin on LV diastolic functional parameters of T2DM patients with stable HF at five institutions in Japan. Echocardiography was performed at baseline and 6 months after administration of dapagliflozin. LV diastolic function was defined as the ratio of mitral inflow E to mitral e′ annular velocities (E/e′). LV longitudinal myocardial function was assessed as global longitudinal strain (GLS), which in turn was determined as the averaged peak longitudinal strain from standard LV apical views. RESULTS: E/e′ significantly decreased from 9.3 to 8.5 cm/s 6 months after administration of dapagliflozin (p = 0.020) as previously described, while GLS showed significant improvement from 15.5 ± 3.5% to 16.9 ± 4.1% (p < 0.01) 6 months after administration of dapagliflozin. Furthermore, improvement of GLS in HF with preserved ejection fraction patients was more significant from 17.0 ± 1.9% to 18.7 ± 2.0% (p < 0.001), compared to that in HF with mid-range ejection fraction and HF with reduced ejection fraction patients from 14.4 ± 2.4% to 15.5 ± 1.8% (p = 0.06) and from 8.1 ± 1.5% to 7.8 ± 2.1% (p = 0.44), respectively. It was noteworthy that multiple regression analysis showed that the change in GLS after administration of dapagliflozin was the only independent determinant parameters for the change in E/e′ after administration of dapagliflozin. CONCLUSION: Dapagliflozin was found to be associated with improvement of LV longitudinal myocardial function, which led to further improvement of LV diastolic function of T2DM patients with stable HF. GLS-guided management may thus lead to improved management of T2DM patients with stable HF.